2019
DOI: 10.1002/anie.201912363
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Surface Charge Regulation in Ionic Covalent Organic Nanosheets: Reversible Exfoliation and Controlled Bacterial Growth

Arindam Mal,
Samiyappan Vijayakumar,
Rakesh K. Mishra
et al.

Abstract: Poor control on the exfoliation of covalent organic frameworks (COFs) remains a disadvantage for their application as two‐dimensional nanosheets. An equally important problem is the reversible control at the available surface charges on COFs. Herein, a strategy for the reversible exfoliation, re‐stacking, and surface‐charge control of a propidium iodide based ionic covalent organic framework, PI‐TFP, using cucurbit[7]uril (CB[7]) induced molecular recognition, is reported. The surface charge on PI‐TFP facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 69 publications
0
47
0
Order By: Relevance
“…87 In a follow up study the related propidium iodide cationic COF was prepared and it readily self-exfoliated in water to sheets with an average thickness of 1.6 nm. 88 Interestingly, this material can be restacked by the use of a macrocyclic host, in this case cucurbit [7]uril, through complexation of the quaternary ammonium groups on the propidium side groups. Addition of 1-adamantylamine hydrochloride leads to decomplexation and the material exfoliates again.…”
Section: D Covalent Organic Frameworkmentioning
confidence: 99%
“…87 In a follow up study the related propidium iodide cationic COF was prepared and it readily self-exfoliated in water to sheets with an average thickness of 1.6 nm. 88 Interestingly, this material can be restacked by the use of a macrocyclic host, in this case cucurbit [7]uril, through complexation of the quaternary ammonium groups on the propidium side groups. Addition of 1-adamantylamine hydrochloride leads to decomplexation and the material exfoliates again.…”
Section: D Covalent Organic Frameworkmentioning
confidence: 99%
“…Inspired by these unique features, we envision that tailoring microenvironment around the active sites of MOF‐based nanozymes via installing specific functional groups and constructing favorable spatial structure may be a promising strategy to make them more closely mimic the natural enzymes. Covalent organic frameworks (COFs), as crystalline organic porous polymers with customizable composition and controlled morphology, have been exploded as salient materials for diverse catalytic reactions and many facets of the biomedical fields [30–38] . For example, several COF‐based hybrid materials with high catalytic performance have been reported, the resultant hierarchical structures could promote the adsorption of reactant substrate molecules [39–41] .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Mal et al have developed a propidium iodide based 2D-iCONs which efficiently inhibit bacterial growth once exfoliated while chemical mediated restacking of the nanosheets switch to loss of their anti-bacterial activity which can further be regenerated by removing the chemical providing a control over bacterial growth. [138] Other sets of anti-bacterial 2D COFs are reported by Liu et al which can kill bacteria in presence of light. [139] Authors have demonstrated that 100 µg/L of these two 2D COFs can kill 90% of bacteria when illuminated with light for 60-90 min.…”
Section: Other Biomedical Applicationsmentioning
confidence: 99%